2001
DOI: 10.18084/1084-7219.6.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effectiveness of Teaching Techniques with Lesbian and Gay Content in the Social Work Curriculum

Abstract: This study investigated the levels of homophobia before and after a single lecture on the topic in one undergraduate and two graduate social work classes. Using the Index of Attitudes Towards Homosexuals (IAH), pretest levels of homophobia were found to exceed the cutting point of 50 for 75% of the students in the undergraduate class. Although pretest-posttest mean scores were not found to be statistically significant, the percentage of students exceeding the IAH cutting score decreased in all three courses fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Accordingly, social work education efforts, especially in the Namibian context, would be well-served by involving personal stories and face-to-face examples given first-hand by LGBT people. In other contexts this education strategy has been associated with improved attitudes among social work students (Cramer, Oles, and Black 1997;Cramer 1997;Dongvillo and Ligon 2001;Chonody, Siebert, and Rutledge 2009). …”
Section: Implications For Social Work Educationmentioning
confidence: 99%
“…Accordingly, social work education efforts, especially in the Namibian context, would be well-served by involving personal stories and face-to-face examples given first-hand by LGBT people. In other contexts this education strategy has been associated with improved attitudes among social work students (Cramer, Oles, and Black 1997;Cramer 1997;Dongvillo and Ligon 2001;Chonody, Siebert, and Rutledge 2009). …”
Section: Implications For Social Work Educationmentioning
confidence: 99%
“…Four studies indicated 50% or more, but less than 70%, white participants in the study sample (Black et al, 1996;Black et al, 1998;Logie et al, 2007;Sun, 2002). Three studies did not report race (Dongvillo & Ligon, 2001;Floyd & Gruber, 2011;Tate, 1991). Similar to the disparities in racial composition, most of the studies had an overrepresentation of women.…”
Section: Participantsmentioning
confidence: 99%
“…Six studies focused on changing students' attitudes through participation in a pedagogical intervention or social work course work (Bassett & Day 2003;Black, Oles, Cramer, & Bennett, 1999;Black, Oles, & Moore, 1996;Cramer, 1997;Cramer, Oles, & Black, 1997;Dongvillo & Ligon, 2001).…”
Section: Aimsmentioning
confidence: 99%
See 2 more Smart Citations